POTENSI HASIL CABAI MERAH (Capsicum annum L) GALUR M2 PADA DOSIS RADIASI SINAR GAMMA - Harta, Rika Yusli; Bella, Rahmi Aurya; Maulia, Era (Institute of Computer Science (IOCS), 2025)
Public demand for red chili is quite high, but the production of fresh red chili in Indonesia from year to year shows a significant decrease. Overcoming this requires chili peppers that can grow in all seasons and various types of land and have high yields. Plant breeding methods that can increase genetic diversity in order to obtain the genetic resources needed to develop types of chili peppers that can thrive on peatlands. Mutation is a useful technique that could be used to increase genetic variability of chili as a basis for developing new improved varieties. One way in plant breeding that aims to increase genetic variation is mutation induction. The method of red chili plants and to identify the dose that produces the greatest effect. A non-factorial randomized block design with three replications was employed in this study. The factors studied were 5 treatment levels consisting of G1 = 100gy, G2 = 200gy, G3 = 300gy, G4 = 400gy and G0 = Pioneer red chili varieties as a comparison, repeated 3 times to obtain 15 samples. Each sample consisted of 2 plants for a total of 30 plants. The study showed that gamma-ray radiation had a highly significant impact on fruit number and a significant effect on fruit weight in red chili plants, with 400 Gy identified as the optimal dose The potential yield of red chili plants was significantly influenced by gamma-ray radiation, with the most effective dose being 400 Gy. Exposure to gamma rays with a dose of 400 Gy is the most optimal dose in producing mutant chili plants from pioneer varieties that are resistant to viral infections.